Gemtuzumab Ozogamicin in Acute Myeloid Leukemia: Efficacy, Toxicity, and Resistance Mechanisms—A Systematic Review - Aurelia Collados-Ros; Manuel Muro; Isabel Legaz (Biomedicines, 2024)
Acute myeloid leukemia (AML) is a diverse group of leukemias characterized by the uncontrolled proliferation of clonal neoplastic hematopoietic precursor cells with chromosomal rearrangements and multiple gene mutations and the impairment of normal hematopoiesis. Current efforts to improve AML outcomes have focused on developing targeted therapies that may allow for improved antileukemic effects while reducing toxicity significantly. Gemtuzumab ozogamicin (GO) is one of the most thoroughly studied molecularly targeted therapies in adults. GO is a monoclonal antibody against CD33 IgG4 linked to the cytotoxic drug calicheamicin DMH. The use of GO as a chemotherapeutic agent is not generalized for all patients who suffer from AML, particularly for those whose health prevents them from using intensive conventional chemotherapy, in which case it can be used on its own, and those who have suffered a first relapse, where its combination with other chemotherapeutic agents is possible. This systematic review aimed to comprehensively evaluate GO, focusing on its molecular structure, mode of action, pharmacokinetics, recommended dosage, resistance mechanisms, and associated toxicities to provide valuable information on the potential benefits and risks associated with its clinical use. A systematic review of eight scientific articles from 2018 to 2023 was conducted using PRISMA analysis. The results showed that GO treatment activates proapoptotic pathways and induces double-strand breaks, initiating DNA repair mechanisms. Cells defective in DNA repair pathways are susceptible to GO cytotoxicity. GO has recommended doses for newly diagnosed CD33+ AML in combination or as a single agent. Depending on the treatment regimen and patient status, GO doses vary for induction, consolidation, and continuation cycles. Multidrug resistance (MDR) involving P-glycoprotein (P-gp) is associated with GO resistance. The overexpression of P-gp reduces GO cytotoxicity; inhibitors of P-gp can restore sensitivity. Mitochondrial pathway activation and survival signaling pathways are linked to GO resistance. Other resistance mechanisms include altered pharmacokinetics, reduced binding ability, and anti-apoptotic mechanisms. GO has limited extramedullary toxicity compared to other AML treatments and may cause hepatic veno-occlusive disease (HVOD). The incidence of hepatic HVOD after GO therapy is higher in patients with high tumor burden. Hematological side effects and hepatotoxicity are prominent, with thrombocytopenia and neutropenia observed. In conclusion, GO’s reintroduction in 2017 followed a thorough FDA review considering its altered dose, dosing schedule, and target population. The drug’s mechanism involves CD33 targeting and calicheamicin-induced DNA damage, leading to apoptosis and resistance mechanisms, including MDR and survival signaling, which impact treatment outcomes. Despite limited extramedullary toxicity, GO is associated with hematological side effects and hepatotoxicity.